Variation in common carotid artery, with special reference to superior thyroid artery: A retrospective angiographic study from central India - Manisha B. Sinha; Gopal Gupta; N.N. Kolhe; H.P. Sinha; N. Gautam (Al Ameen Medical College, 2022)
Introduction: Common carotid artery is a gateway to the blood supply to the head and neck region, including the brain. Previous cadaveric and few radiological studies have shown variation in the level of division and varying patterns of branches of the common carotid artery. Aim: The aim of the study is to investigate the prevalence of the commonest level of division of CCA in vivo through the use of CT angiography and the distance of STA (superior thyroid artery) from the level of bifurcation. Material and method: A total of 88 angiograms evaluated for study purpose, both right & left-sided views of the neck of all the 44 patients, have been taken into consideration during three years. Patients with intraparenchymal bleed and stroke, who had undergone CT angiography of the head and neck region, were selected and evaluated for study. Result: In the present study, the most frequent site of bifurcation of CCA was found to be type-II, which was at the level above the greater cornua of the hyoid bone (43.18%), and the least common site was type-V, which was at the level below the superior border of thyroid cartilage (1.13%). Conclusion: Variation in the bifurcation level of CCA results in variation in the origin and other parameters of other vessels (especially STA in this case) originating from the carotid arterial trunk. It leads to the possibility of misleading information to the clinicians during surgical and radiological procedures.